Effects of Acute and Chronic Exercise on Immunological Parameters in the Elderly Aged: Can Physical Activity Counteract the Effects of Aging? - Sellami, Maha; Gasmi, Maha; Denham, Joshua; Hayes, Lawrence D.; Stratton, Dan; Padulo, Johnny; Bragazzi, Nicola (Frontiers in Immunology, 2018)
Immunosenescence is characterized by deterioration of the immune system caused by ageing which induces changes to innate and adaptative immunity. Immunossence affects function and phenotype of immune cells, such as expression and function of receptors for immune cells which contributes to loss of immune function (chemotaxis, intracellular killing). Moreover, these alterations decrease the response to pathogens and vaccines, which leads to several age-related diseases including cardiovascular disease, Alzheimer’s disease, and diabetes in older individuals. Furthermore, increased risk of autoimmune disease and chronic infection is also manifest, which promotes a pro-inflammatory cellular environment, ultimatelyleading to accelerates biological ageing. During the last century, sedentaryism rose dramatically, with a comcomittent increase in certain type of cancer and autoimmune disease. Numerous studies on physical activity and immunity with focus on special population (i.e. diabetics, VIH patient) demonstrate chronic exercise enhances immunity. However, most previous work has focused on either pathological population or healthy young adults whilst research in elderly population is scarce. Rresearch conducted to date has primarily focused on aerobic and reistance exercise training and its effect on immunity. This review focuses on the potential for exercise training to affect the aging immune system. The concept is that some lifestyle strategies such as high-intensity exercise training may prevent disease through the attenuation of immunosenescence. In this context, we take a top down approach and review the effect of exercise and training on immunological parameters in elderly at rest and during exercise in humans, and how they respond to different modes of training. We highlight the impact of these different exercise modes on immunological parameters, such as cytokine and lymphocyte concentration in elderly individuals.